1995
DOI: 10.1002/pro.5560040811
|View full text |Cite
|
Sign up to set email alerts
|

Control of aggregation in protein refolding: A variety of surfactants promote renaturation of carbonic anhydrase II

Abstract: The denaturation and renaturation of carbonic anhydrase I1 (CAII) has been studied in several laboratories. Both thermodynamic and kinetic evidence support the existence of at least two intermediates between denatured and native protein. Previous studies have shown that on rapid dilution of a CAII solution from 5 M to 1 M guanidinium chloride, aggregation strongly competes with renaturation at higher protein concentrations, suggesting an upper limit for [CAII] of -0.1%. Our experiments show 60% renaturation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 30 publications
(32 reference statements)
8
125
1
Order By: Relevance
“…It aggregates during renaturation when denatured with heat 26 or acid, 27 or when incubated in intermediate concentrations (1-3 M) of guanidinium chloride (GuHCl). [28][29][30] For example, Hammarström et al observed low (<10%) recovery of activity of human carbonic anhydrase (HCAII) when it was renatured by dilution from 2 to 0.3 M GuHCl, but high (>80%) recovery of activity when diluted from 6 M GuHCl to 0.3 M. 30 McCoy et al 26 also observed aggregation of BCA in refolding of the protein, denatured in a solution of 0.1% SDS and renatured with dialysis. 31 We believe that irreversible aggregation interferes with refolding of BCA (and BCA-Ac 18 ) in intermediate concentrations of SDS and prevents equilibration (eq 1).…”
Section: Why Do We Not Achieve Equilibration Between Native and Denatmentioning
confidence: 99%
“…It aggregates during renaturation when denatured with heat 26 or acid, 27 or when incubated in intermediate concentrations (1-3 M) of guanidinium chloride (GuHCl). [28][29][30] For example, Hammarström et al observed low (<10%) recovery of activity of human carbonic anhydrase (HCAII) when it was renatured by dilution from 2 to 0.3 M GuHCl, but high (>80%) recovery of activity when diluted from 6 M GuHCl to 0.3 M. 30 McCoy et al 26 also observed aggregation of BCA in refolding of the protein, denatured in a solution of 0.1% SDS and renatured with dialysis. 31 We believe that irreversible aggregation interferes with refolding of BCA (and BCA-Ac 18 ) in intermediate concentrations of SDS and prevents equilibration (eq 1).…”
Section: Why Do We Not Achieve Equilibration Between Native and Denatmentioning
confidence: 99%
“…CAB preferred ionic detergent as the ¢rst agent (Table 2). Cetyltrimethylammonium bromide (CTAB) and N-tetradecyl-N,N-dimethyl-3-ammonio-1-propanesulfonate (SB [3][4][5][6][7][8][9][10][11][12][13][14] were the most e¡ective detergents. Fortunately, cycloamylose also worked well in stripping these ionic detergents and promoting refolding of CAB at a high yield.…”
Section: Refolding Of Cab and Lysozymementioning
confidence: 99%
“…One common approach, known as the`dilution additive strategy', has been to include low molecular weight folding assistants in the bu¡er used to dilute the chemically denatured protein. A number of in vitro aggregation inhibitors or folding aids such as polyethylene glycol [4], polyamino acids [5], cyclodextrins [6] and detergents [7] have been reported to prevent aggregation and enhance protein folding.…”
Section: Introductionmentioning
confidence: 99%
“…Physical factors include temperature, pH and pressure [10 -12]. Chemical factors (solvent denaturation) include high concentrations of chaotropic agents such as urea and guanidine hydrochloride (GuHCl) [2,13,14], certain miscible organic solvents such as alcohol or acetone [10], detergents and surfactants such as sodium dodecyl sulphate (SDS) and dodecyl trimethyl ammonium bromide (DTAB) [15,16]. Since the native conformation of a protein molecule is held together by a large number of bonds, it is therefore conceivable that the disruption of these bonds may require different denaturing conditions with different rates under the same conditions.…”
Section: Introductionmentioning
confidence: 99%